ANALYSIS OF PHRASEOLOGICAL UNITS EXPRESSING TIME COMPONENTS IN ENGLISH AND UZBEK LANGUAGES - Ishonqulov Sherzod Usmonovich (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study presents a comparative-typological analysis of time-related phraseological units (idioms, proverbs, and set expressions) in English and Uzbek. Time is a universal category, yet its linguistic manifestation is deeply rooted in the cultural and historical consciousness of a nation. By examining the semantic, structural, and cultural characteristics of these units, the research identifies universal conceptual constants and language-specific nuances. The findings reveal that while both languages use spatial metaphors to describe time, English phraseology often emphasizes the economic value of time (time is money), whereas Uzbek phraseology frequently links time to moral patience and divine destiny.